Disentangling the Disabling Process: Insights From the Precipitating Events Project - Gill, Thomas M. (Oxford University Press, 2014)
Among older persons, disability in activities of daily living is common and highly morbid. The Precipitating Events Project (PEP Study), an ongoing longitudinal study of 754 initially nondisabled, community-living persons, aged 70 or older, was designed to further elucidate the epidemiology of disability, with the goal of informing the development of effective interventions to maintain and restore independent function. Over the past 16 years, participants have completed comprehensive, home-based assessments at 18-month intervals and have been interviewed monthly to reassess their functional status and ascertain intervening events, other health care utilization, and deaths. Findings from the PEP Study have demonstrated that the disabling process for many older persons is characterized by multiple and possibly interrelated disability episodes, even over relatively short periods of time, and that disability often results when an intervening event is superimposed upon a vulnerable host. Given the frequency of assessments, long duration of follow-up, and recent linkage to Medicare data, the PEP Study will continue to be an outstanding platform for disability research in older persons. In addition, as the number of decedents accrues, the PEP Study will increasingly become a valuable resource for investigating symptoms, function, and health care utilization at the end of life.